2018
DOI: 10.7595/management.fon.2018.0008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Leadership on Innovation: Evidence from the Hotel Industry

Abstract: Research Question: The paper investigated a relationship between innovation and transformational/transactional leadership, as well as the impact of these two leadership styles on innovation. Motivation: As there are small number of studies that have examined the impact of transformational and transactional leadership on innovations within the hospitality industry and in Serbia, the need for investigation is imposed. The paper draws on methodology and works of Bass and Avolio (1997), Hogan et al. (2011) and Nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Inspirational motivation refers to how leaders can motivate their followers to achieve a state of inspiration that enhances their ingenuity, innovation, and ability to do their utmost to help achieve goals for their organization (Vuković, Damnjanović, Papić-Blagojević, Jošanov-Vrgović, & Gagić, 2018). It is important for leaders to eradicate doubts and fears for their followers through the use of inspirational motivation and encourage them to believe in change for the application of an effective change initiative.…”
Section: Ii) Inspirational Motivationmentioning
confidence: 99%
“…Inspirational motivation refers to how leaders can motivate their followers to achieve a state of inspiration that enhances their ingenuity, innovation, and ability to do their utmost to help achieve goals for their organization (Vuković, Damnjanović, Papić-Blagojević, Jošanov-Vrgović, & Gagić, 2018). It is important for leaders to eradicate doubts and fears for their followers through the use of inspirational motivation and encourage them to believe in change for the application of an effective change initiative.…”
Section: Ii) Inspirational Motivationmentioning
confidence: 99%
“…In a complementary way, the business leadership brings the attribution of reformulating or recreating processes, services, and products in the middle of this cycle. The aspects of inspiration and empowerment generated by Transformational Leadership ultimately lead to the commitment to a vision and action that creates change agents with enhanced perceptions of self-efficacy, inspirational motivation, intellectual stimulation, and creative behaviour (Alamir et al, 2019;Jovičić Vuković et al, 2018). Therefore, transformation leaders are recognised as change agents and visionaries who trust people and can deal with complexity and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Transformational leadership style has also been used in hospitality and tourism sector studies, demonstrated most often in the hospitality sector, working on the positive influences on Innovative behaviour, organisational commitment, and creativity performance (Alamir et al, 2019;Gu et al, 2017;Jovičić Vuković et al, 2018). Therefore, it is known that there are varied leadership styles that, consequently, have different influences.…”
Section: Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this leadership style is important for improving performance (Chen et al, 2020). This is the case because the characteristics of transformational leadership are compatible with the principles and values of QM and because it promotes the creativity of employees to introduce improvements and thus enhance performance (Jovicic et al, 2018;Khattak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%